The phenomenology of the dwelling space in Robert Frost's poetry - Rawashdeh, Faisal I.; Zuraikat, Malek J. (Penerbit Universiti Kebangsaan Malaysia, 2018)
In many of his poems, Robert Frost deploys space, rather than time or the narrative episode, to anchor the tragic, which we define as the lack of the habitable attributes of the dwelling space. Frost brings the domestic tragic into a high degree of prominence, sketching for his readers a spatial reality that is situated within the parameters of the dwelling space. To him, this interaction with space defines a permanent struggle on the part of human beings to create a habitable environment, one that embodies the true essence of dwelling. Following from a critical conversation on spatiality and dwelling, we appropriate Gaston Bachelard’s and Martin Heidegger's phenomenological notions of homeness and non-homeness to interpret Frost's nuanced spatial dramatizations and his poetics of dwelling. Informed by the critical insights of these two thinkers, we argue that Frost's spatial dramatizations describe a polarized, irrational environment where the notion of homeness is built upon non-homeness and where the dweller is unable to understand his/her relationship with the dwelling space. We thus bring attention to Frost as a modernist poet significantly contributing to the critical conversation and phenomenological tradition on modern spaces and the modern experience of homeness/nonhomeness.